2018
DOI: 10.1111/ijd.14003
|View full text |Cite
|
Sign up to set email alerts
|

Subungual exostosis and subungual osteochondromas: a description of 25 cases

Abstract: Clinically and histopathologically, SE and SO appear to be two different entities. When diagnosed correctly and treated appropriately, the lesions have good functional and cosmetic results, as well as a very low recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 15 publications
4
33
0
3
Order By: Relevance
“…In most cases, the SO affected the hallux. In line with our results, Göktay et al [23] showed that the majority of SO subjects were women.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In most cases, the SO affected the hallux. In line with our results, Göktay et al [23] showed that the majority of SO subjects were women.…”
Section: Discussionsupporting
confidence: 94%
“…The most frequently reported complication was dystrophic nails and, regarding the ethology of this disorder, trauma was reported as the first cause [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray graphy should be performed in cases of nail distrophy that KOH examination is negative and particularly in cases whose distrophy is in a single nail. The surgical operation should be performed after the diagnosis is made (56).…”
Section: Radiological Examinationsmentioning
confidence: 99%
“…[2][3][4] They are, altogether with subungual exostosis, the most common bony lesions affecting the nail unit. 5 Some authors consider subungual exostosis a variant of osteochondroma or even a single entity 1,5,6 whereas others have described differences among them 7,8 one of these being its US findings (Table 1).…”
Section: Introductionmentioning
confidence: 99%